Job Creation and the Role of Dependencies - Paolo Fornaro; Henri Luomaranta (The Research Institute of the Finnish Economy (ETLA), 2016)
We contribute to the extensive literature on the relationship between firm size and job creation, by examining the effects of dependencies between enterprises. Using Finnish monthly data encompassing the population of Finnish private businesses, we calculate the gross job creation and destruction, together with the net job creation, for different size classes and industries. Importantly, we divide firms into a dependent (i.e. owned, at least partially, by a large company) and independent category. Due to the quality of the data, we are able to isolate the 'organic' growth of firms, disregarding the effects of mergers, split-offs and other legal restructuring. We find that independent companies have shown a considerably higher net job creation, regardless of their size class. However, dependent firms do not show particularly different behaviors with respect to the sensitivity to aggregate conditions, compared to their independent counterparts. Once we control for age, we find that independent firms generate more (net) jobs during the early years of their existence but destroy more jobs once they become older.
Keywords: D22; E24; E32; L25; 330; Dependencies; firm size; firm age; employment creation